Groundwater arsenic remediation treatment technology and scale up - Pal, Parimal (Waltham, MA Elsevier, 2015)
Arsenic abatement from groundwater in locations with a central water distribution system is relatively simple. The real challenge is selecting the most effective and affordable treatment and scale up option for locations which lack the appropriate infrastructure. Groundwater Arsenic Remediation: Treatment Technology and Scale UP provides the latest breakthrough groundwater treatment technologies and modeling and simulation methods for project scale up and eventually field deployment in locations which lack the proper central water distribution system to ensure arsenic free groundwater.--Provided by publisher.
Chapter 1 : Introduction to the Arsenic Contamination Problem -- Chapter 2 : Chemical Treatment Methods in Arsenic Removal -- Chapter 3 : Adsorption Method of Arsenic Separation from Water -- Chapter 4 : Arsenic Removal by Membrane Filtration -- Chapter 5 : Arsenic Removal by Membrane Distillation -- Chapter 6 : Disposal of Concentrated Arsenic Rejects -- Chapter 7 : Arsenic Removal Technologies on Comparison Scale and Sustainability Issues -- Index.
Electronic reproduction.
Keywords: Arsenic compounds; Arsenic -- Environmental aspects; Groundwater -- Pollution; Electronic books